SISTEM INFORMASI EVALUASI PELAYANAN PUBLIK PADA PUSKESMAS TINGGEDE DENGAN MENGGUNAKAN METODE INDEKS KEPUASAN MASYARAKAT - Syarifah Fitrah Ramadhani; Sukardi Sukardi; Agus Romadhona; Pujianti Wahyuningsih; Dian Fitianingsih (Electro Luceat, 2022)
One of the public services in the health sector is the puskesmas. Puskesmas is a public service that is very easily accessible to the general public. However, with the number of puskesmas service centers spread across various districts or cities, it becomes a benchmark in knowing the performance of each employee under the auspices of the agency. The level of community satisfaction in responding to services provided at this time at the Tinggede Health Center by using a box that reads satisfied and dissatisfied. The shortfall in the assessment of public services is because there is no basis for the assessment. The solution in overcoming this problem, the researchers built a web-based information system that can be used at the puskesmas in evaluating satisfaction with the service provided to the community with a satisfaction index based on the MenPan-RB decision number 14 of 2017. The level of success in measuring the information system built with using black box testing and Likert scale. The number of responses in this study were 28 people with the results of the black box testing reaching 100% and the Likert scale reaching a value of 79.5%.